Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
1)
[tex](-2+\sqrt{-5})^2\implies (-2+\sqrt{-1\cdot 5})^2\implies (-2+\sqrt{-1}\sqrt{5})^2\implies (-2+i\sqrt{5})^2 \\\\\\ (-2+i\sqrt{5})(-2+i\sqrt{5})\implies +4-2i\sqrt{5}-2i\sqrt{5}+(i\sqrt{5})^2 \\\\\\ 4-4i\sqrt{5}+[i^2(\sqrt{5})^2]\implies 4-4i\sqrt{5}+[-1\cdot 5] \\\\\\ 4-4i\sqrt{5}-5\implies -1-4i\sqrt{5}[/tex]
3)
let's recall that the conjugate of any pair a + b is simply the same pair with a different sign, namely a - b and the reverse is also true, let's also recall that i² = -1.
[tex]\cfrac{6-7i}{1-2i}\implies \stackrel{\textit{multiplying both sides by the denominator's conjugate}}{\cfrac{6-7i}{1-2i}\cdot \cfrac{1+2i}{1+2i}\implies \cfrac{(6-7i)(1+2i)}{\underset{\textit{difference of squares}}{(1-2i)(1+2i)}}} \\\\\\ \cfrac{(6-7i)(1+2i)}{1^2-(2i)^2}\implies \cfrac{6-12i-7i-14i^2}{1-(2^2i^2)}\implies \cfrac{6-19i-14(-1)}{1-[4(-1)]} \\\\\\ \cfrac{6-19i+14}{1-(-4)}\implies \cfrac{20-19i}{1+4}\implies \cfrac{20-19i}{5}\implies \cfrac{20}{5}-\cfrac{19i}{5}\implies 4-\cfrac{19i}{5}[/tex]
Answer:
1) -1-4√(5)*i
2)(8/41)+(10/41)i
3)4+i
4)x=(1/3)±[√(23)/3]i OR x=(1/3)+[√(23)/3]i and x=(1/3)-[√(23)/3]i
Step-by-step explanation:
1) remember the special product:
(a+b)²=a²+2ab+b²
in this situation, a=-2 and b=√(-5)
(-2+√(-5))²=(-2)²+2(-2)(√(-5))+(√(-5))²
=4-4*√(-5)+(-5)
=-1-4√(-5)
√(-5)=-√(5)*i, so the final answer is: -1-4√(5)*i
2) remember the special product:
(a+b)(a-b)=a²-b²
multiply by the conjugate of the denominator (so multiply the numerator and denominator by 4+5i to remove i from the denominator, I'll demonstrate)
2/(4-5i) * (4+5i)/(4+5i)
=2(4+5i)/[(4-5i)(4+5i)]
use the special product; in this situation, a=4 and b=5i
=(8+10i)/[16-(5i)²]
simplify: (5i)²=5²*(√(-1))²=25*-1=-25
(8+10i)/[16-(5i)²]=(8+10i)/[16-(-25)]
=(8+10i)/41
and finally, divide to get the answer in the correct form:
=(8/41)+(10/41)i
you can use a calculator to write 8/41 and 10/41 as decimals instead.
3) again, multiply by the conjugate of the denominator to both the top and the bottom:
(6-7i)/(1-2i) * (1+2i)/(1+2i)
=(6-7i)(1+2i)/[(1-2i)(1+2i)]
now for the multiplication of the numerator:
(6-7i)(1+2i)=6(1+2i)-7i(1+2i)=(6+12i)-(7i+14i²)
i²=-1, so 14i²=-14
(6+12i)-(7i+14i²)=6+12i-7i-(-14)=6+5i+14=20+5i
as for the denominator, do what we did in 2) and use the special product to get:
(1-2i)(1+2i)=1-(2i)²=1-(-4)=5
so the answer is (20+5i)/5
now divide to convert the answer to the proper form/simplify
(20/5)+(5/5)i=4+i
4) use the quadratic formula, this is how you solve second-degree equations that aren't very easy to factor.
the formula: for ax^2+bx+c=0, x=[-b±√(b²-4ac)]/2a
in this case, a=4.5, b=-3, and c=12
plug in the values (± means that there are two solutions, one is when you add, and one is when you subtract.)
x=[-(-3)±√((-3)²-4*4.5*12)]/(2*4.5)
=[3±√(9-216)]/9
=[3±√(-207)]/9
√(-207)=√(207)*√(-1)=√(207)*i
√(207) can be simplified to 3√(23):
√(207)=√(9*23)=√(9)*√(23)=3√(23)
so now:
x=[3±3√(23)*i]/9
divide by 9 to get the answer in the correct form:
x=(3/9)±[(3√(23))/9]i
x=(1/3)±[√(23)/3]i
you can also rewrite this as x=(1/3)+[√(23)/3]i and x=(1/3)-[√(23)/3]i (just make sure to include both answers)
hopefully that helped! more practice will make these kinds of problems much easier :)
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.